P-264 Verification of expected death: a training intervention for registered nurses in kent and sussex. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Prevost, Nicola Le; Kirk, Mary; Joyce, Jaqueline
Abstract : Background: National and local experience with anecdotal reports demonstrate adult end of life care guidance (NICE, 2017) not being achieved for verification of expected death (VoED). Response by Hospice UK collaboratively developing and launching Care After Death publication (2017) new guidance for Registered Nurses (RNs) on VoED. Concern about VoED practice issue at Kent EoLC education meeting resulting in delivering an educational intervention funded by Health Education England shared by local hospices. Practice Issues: Late verification in the community has a distressing impact on families/carers. Contributing factor 'staff are not clear about the legal requirements surrounding the procedure' (Merrifield, 2016). Aims: Build the confidence and competence of RNs undertaking VoED. Align training with Hospice UK guidance. Increased number of practitioners with the required skills, knowledge and competence. Reducing reliance on medical practitioners. Methods: The education initiative comprises: taught face to-face group session of at least three hours. completion of a workbook. completion of competence assessment. The workbook has been designed as a support tool to embed learning and provide evidence of reflection and competence. Pre-course and post-course confidence questionnaires are completed by attendees, followed up for post-course attendance. Findings: The pre- and post- course questionnaires indicate a shift towards increased confidence in undertaking VoED. Workbooks have been well received. More detailed findings are not available at the current time due to the project commencement, further data will be available by the time of presentation. Anticipated data will continue to demonstrate increased confidence in RNs. Increased numbers of RNs will be undertaking VoED in the locality. Conclusion: Project demonstrates the highlighting of an area of concern around patient and family experience and addressed, with regional resource support plus collaborative working leading to improving family and carer experience of expected death in the community. With increased numbers of RNs with the confidence and competence to undertake VoED then the NICE guidance should be met.